Bronchoscopic Appearance of Tracheal Adenoid Cystic Carcinoma - Surani, Salim; Ahmed, Maqsood; Mullin, James; Varon, Joseph (Current Respiratory Medicine Reviews, 2006)
Primary tracheal malignancies are very infrequent, and data relating to them is limited. We recently encountered an 82 yearold woman with a history of aortic stenosis, hypertension, and hypothyroidism, that presented to the clinic with cough and shortness of breath of six month duration. A computed tomography (CT) scan of the chest revealed tracheal thickening with nonspecific nodularity. The patient underwent fiberoptic bronchoscopy that revealed a tracheal mass with significant airway narrowing (Fig. 1). Biopsy of the tracheal mass revealed a tumor composed of small-to-medium size nests that contained lumen -forming eosinophil cells centrally, and smaller basaloid cells peripherally (Fig. 2). The cystic spaces within the basaloid cells made the diagnosis of adenoid cystic carcinoma. There was no evidence of tumor spread on positron emission tomography (PET) scan. Because of the extent of the lesion and in view of her pre-existing conditions, the patient elected non-operative treatment. Adenoid cystic carcinomas in the trachea are rare, but represent around 40% of all tracheal tumors.
Keywords: Primary tracheal malignancies